EXPERIMENTS WITH FIBRE-GLASS SHEATHING AS A PROTECTION AGAINST MARINE WOOD BORING ORGANISMS - BALASUBRAMANYAN, R (Fishery Technology, 2025)
Wooden test panels of different species of wood sheathed with fibre-glass reinforced plastic were subjected to immersion tests along with corresponding controls in Cochin Port area and the effect of the protective coating studied.